2021
DOI: 10.21203/rs.3.rs-80716/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observation of The Curative Effect of Guizhi-Shaoyao-Zhimu Decoction Combined With Methotrexate In The Treatment of Early Rheumatoid Arthritis Based On Ultrasonic Evaluation: Study Protocol of A Randomized, Double-Blind, Controlled Clinical Trial

Abstract: Background: Rheumatoid arthritis(RA) is a chronic inflammatory autoimmune disease with the primary clinical symptoms of joint swelling and pain. Early detection of erosion and synovial inflammation at an active stage resulting from RA can prevent damage to the joints and activity restriction. However ,there are still many patients who do not respond to these treatments, the development of newer, safer drugs is urgently needed. Compared to Western medicine, Guizhi-Shaoyao-Zhimu decoction has equal or higher eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previous research has reported that GSZD can reduce the levels of pro-inflammatory factors TNF-α, IL-1β, IL-17 and receptor activator for NF-κB ligand (RANKL), thus inhibiting the recruitment and differentiation of osteoclast precursors. GSZD may also increase the secretion of osteoclastogenesis inhibitory factor (OPG), thereby regulating the ratio of RANKL/OPG that could promote the protection of bone to improve the injury of cartilage and synovium in CIA rats ( 51 ). In the present study, ‘Gu Sui Bu’ (Rhizoma Drynariae), ‘Bu Gu Zhi’ (Fructus Psoraleae) and ‘Sang Zhi’ (Ramulus Mori) were added to the original medicinal preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that GSZD can reduce the levels of pro-inflammatory factors TNF-α, IL-1β, IL-17 and receptor activator for NF-κB ligand (RANKL), thus inhibiting the recruitment and differentiation of osteoclast precursors. GSZD may also increase the secretion of osteoclastogenesis inhibitory factor (OPG), thereby regulating the ratio of RANKL/OPG that could promote the protection of bone to improve the injury of cartilage and synovium in CIA rats ( 51 ). In the present study, ‘Gu Sui Bu’ (Rhizoma Drynariae), ‘Bu Gu Zhi’ (Fructus Psoraleae) and ‘Sang Zhi’ (Ramulus Mori) were added to the original medicinal preparation.…”
Section: Discussionmentioning
confidence: 99%